Morphophysiology of guava rootstock irrigated with salted water under nitrogen doses - Silva, Evandro Manoel da; Nobre, Reginaldo Gomes; Souza, Leandro dePádua; Araújo, Railene Hérica Carlos Rocha; Pinheiro, Francisco Wesley Alaves; Almeida, Luana Lucas de Sá (Comunicata Scientiae, 2017)
The irrigation with saline water reduces crop growth and yield, resulting in the need of new techniques that enable the use of this natural resource in fruit growing. In this sense, the objective of this study was to evaluate the effect of saline irrigation water associated with different nitrogen doses on guava rootstock cv. Paluma morphophysiology. The experiment was carried out in a completely randomized blocks design, testing 5 electrical conductivity of irrigation water - ECw (0.3, 1.1, 1.9, 2.7 and 3.5 dS m-1) and four nitrogen doses for fertilization (541.1; 773.0; 1004.9 and 1236.8 mg dm-3), in a 5x4 factorial, with four repetitions. The increase in the ECw from 0.3 dS m-1 negatively affected the morphophysiology of guava rootstock cv. Paluma, especially during the younger phase of the crop. The N dose of 541 mg dm-3 stimulated the increase of most morphophysiological variables in guava rootstock during the period studied. The nitrogen fertilization did not reduced the salt stress effect on the evaluated variables.